2020
DOI: 10.3390/diagnostics10060389
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Ovarian Adenocarcinoma Cells with Cisplatin-Resistance by Feature Extraction of Gray Level Co-Occurrence Matrix Using Optical Images

Abstract: Ovarian cancer is the most malignant of all gynecological cancers. A challenge that deteriorates with ovarian adenocarcinoma in neoplastic disease patients has been associated with the chemoresistance of cancer cells. Cisplatin (CP) belongs to the first-line chemotherapeutic agents and it would be beneficial to identify chemoresistance for ovarian adenocarcinoma cells, especially CP-resistance. Gray level co-occurrence matrix (GLCM) was characterized imaging from a numeric matrix and find its texture features.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The obtained results showed that it is possible to predict the presence of early-stage breast cancer with high spatial resolution using SWIR and the phantom model in which the optical parameters are implemented in the breast structure [ 3 ]. Huang and colleagues proposed a promising method based on the gray level co-occurrence matrix (GLCM) image processing model to achieve a rapid technique with a more reliable diagnostic performance for various types of chemoresistance for the cisplatin of human ovarian adenocarcinoma cells by feature extraction of GLCM [ 4 ].…”
mentioning
confidence: 99%
“…The obtained results showed that it is possible to predict the presence of early-stage breast cancer with high spatial resolution using SWIR and the phantom model in which the optical parameters are implemented in the breast structure [ 3 ]. Huang and colleagues proposed a promising method based on the gray level co-occurrence matrix (GLCM) image processing model to achieve a rapid technique with a more reliable diagnostic performance for various types of chemoresistance for the cisplatin of human ovarian adenocarcinoma cells by feature extraction of GLCM [ 4 ].…”
mentioning
confidence: 99%
“…The values are evaluated on repeated execution of the proposed model with a varied training level. The performance of the proposed model is compared against a Heuristic Approach for Real-Time Image Segmentation (HARIS) [ 25 ], a Fine-Tuned Neural Networks (FTNN) approach [ 77 ], a Convolutional Neural Network (CNN) [ 32 ], the VGG-19 model [ 78 ], and MobileNet models [ 72 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…One strategy of texture attribute extraction is the Grey-Level Co-occurrence Matrix (GLCM) [ 72 ] approach with the localized intensity coefficient’s recurring sequence. GLCM gives the spatial distribution structure of the color and intensity of the pixel, which is determined by the distribution of intensity levels within the window.…”
Section: Methodsmentioning
confidence: 99%
“…Huang et al . (52) also used the GLCM approach to identify textural features on ovarian adenocarcinoma cells indicative of chemoresistance. Specifically, the GLCM was used to calculate contrast, energy, entropy, and homogeneity, variables that collectively can reveal the disordered surface morphology characteristic of cancer cells.…”
Section: Discussionmentioning
confidence: 99%